Learning with multiple external representations in physics : Concreteness fading versus simultaneous presentation - Lichtenberger, Andreas (John Wiley & Sons, 2025)
Multiple external representations (MERs) are useful for teaching complex content in science education. An open question is whether there is an especially effective way to sequence MERs. On the one hand, the so-called concreteness fading approach suggests starting instruction with more concrete representations and proceeding stepwise to more idealized representations. The effectiveness of this fading approach is, however, supported mainly by studies in mathematics education, while the results in physics are equivocal. On the other hand, presenting different representations simultaneously may support linking, that is, the comparison and contrast of representations, which may benefit learning. In an experimental classroom study (N = 187), we compared concreteness fading and simultaneous presentation of MERs for learning a challenging physics content in high school, namely, Faraday's law. We found no significant differences between conditions in posttest performance, and an equivalence test with bounds d = -0.5 to 0.5 showed that both approaches performed equally. The results align with previous findings questioning the superiority of concreteness fading over other ways of sequencing MERs. Therefore, facilitating students' understanding of a complex physics content may involve more than determining the optimal order of presenting MERs. We discuss limitations of the present study and implications for future research and practice.